Genome-based reclassification of azospirillum brasilense SP245 as the type strain of azospirillum baldaniorum sp. nov - Ferreira, Natalia Dos Santos (2020)
Azospirillum sp. strain Sp245T, originally identified as belonging to Azospirillum brasilense, is recognized as a plant-growth-promoting rhizobacterium due to its ability to fix atmospheric nitrogen and to produce plant-beneficial compounds. Azospirillum sp. Sp245T and other related strains were isolated from the root surfaces of different plants in Brazil. Cells are Gram-negative, curved or slightly curved rods, and motile with polar and lateral flagella. Their growth temperature varies between 20 to 38 °C and their carbon source utilization is similar to other Azospirillum species. A preliminary 16S rRNA sequence analysis showed that the new species is closely related to A. brasilense Sp7T and A. formosense CC-Nfb-7T. Housekeeping genes revealed that Azospirillum sp. Sp245T, BR 12001 and Vi22 form a separate cluster from strain A. formosense CC-Nfb-7T, and a group of strains closely related to A. brasilense Sp7T. Overall genome relatedness index (OGRI) analyses estimated based on average nucleotide identity (ANI) and digital DNA–DNA hybridization (dDDH) between Azospirillum sp. Sp245T and its close relatives to other Azospirillum species type strains, such as A. brasilense Sp7T and A. formosense CC-Nfb-7T, revealed values lower than the limit of species circumscription. Moreover, core-proteome phylogeny including 1079 common shared proteins showed the independent clusterization of A. brasilense Sp7T, A. formosense CC-Nfb-7T and Azospirillum sp. Sp245T, a finding that was corroborated by the genome clustering of OGRI values and housekeeping phylogenies. The DNA G+C content of the cluster of Sp245T was 68.4–68.6%. Based on the phylogenetic, genomic, phenotypical and physiological analysis, we propose that strain Sp245T together with the strains Vi22 and BR12001 represent a novel species of the genus Azospirillum, for which the name Azospirillum baldaniorum sp. nov. is proposed. The type strain is Sp245T (=BR 11005T=IBPPM 219T) (GCF_007827915.1, GCF_000237365.1, and GCF_003119195.2).